2007
DOI: 10.3139/146.101576
|View full text |Cite
|
Sign up to set email alerts
|

Examination of phase transformations in the system Fe–N–C by means of nitrocarburising reactions and secondary annealing experiments; the α + ∊ two-phase equilibrium

Abstract: The until now controversially discussed existence of the two-phase equilibrium α-Fe + ∊-Fe3(N, C)1+x in the ternary system Fe – N – C was proven by the investigation (optical microscopy, X-ray diffraction, Electron Backscatter Diffraction) of compound-layer microstructures generated by gaseous nitrocarburising of pure iron and subsequent secondary annealing experiments under static inert-gas atmosphere. The invariant transition reaction γ-Fe4N + Fe3C → α-Fe + ∊-Fe3(N, C)1+x could be shown to proceed at a (sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…[15] In contrast to these early experimental works, [34][35][36] the observation of microstructures forming upon nitriding of Fe-C alloys and C-containing steels and upon nitrocarburizing pure Fe, Fe-C alloys, and C-containing steels, which do contain interfaces between a and e [37][38][39][40][41][42][43][44][45][46][47] makes it very likely that equilibrium between a and e does occur, albeit in a narrow temperature range. Later works [15,[48][49][50][51][52][53] confirmed the occurrence of such microstructures. Except for an early work, [54] the a + e equilibrium is taken into account in all thermodynamic descriptions of the Fe-N-C system in the literature.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[15] In contrast to these early experimental works, [34][35][36] the observation of microstructures forming upon nitriding of Fe-C alloys and C-containing steels and upon nitrocarburizing pure Fe, Fe-C alloys, and C-containing steels, which do contain interfaces between a and e [37][38][39][40][41][42][43][44][45][46][47] makes it very likely that equilibrium between a and e does occur, albeit in a narrow temperature range. Later works [15,[48][49][50][51][52][53] confirmed the occurrence of such microstructures. Except for an early work, [54] the a + e equilibrium is taken into account in all thermodynamic descriptions of the Fe-N-C system in the literature.…”
Section: Introductionmentioning
confidence: 75%
“…Except for an early work, [54] the a + e equilibrium is taken into account in all thermodynamic descriptions of the Fe-N-C system in the literature. [20,22,24,[55][56][57] However, systematic experimental work to investigate the occurrence of the a + e equilibrium [48,53] showed that the experimentally determined temperatures of the invariant reactions leading to the appearance of this equilibrium deviate from the temperatures as predicted using each of the thermodynamic descriptions from the literature. [20,22,24,[55][56][57] Additionally, a recent experimental study of the constitution in the system Fe-N-C for the temperature range above 853 K (580°C), [15] investigating both the phase boundaries and the temperatures of the invariant reactions involving c, showed bad agreement with again each of the thermodynamic descriptions from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in contrast to the binary systems, in the ternary system, the e phase can exist in equilibrium with the a phase at typical nitriding/nitrocarburising temperatures,i nt his case containing relatively large amounts of Cand remarkably small amounts of Nincomparison to the typical Nc ontent of binary e nitride at the same temperature [2,[9][10][11]. This a + e equilibriumwas not included in earlypublications covering the constitution of the system Fe-N-C [ 12,13].…”
Section: Phases In the Fe-n-cs Ystemmentioning
confidence: 99%
“…In later works, [12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] microstructures with a and e in direct contact were frequently found and recognized as such. On this basis, at present an equilibrium of a and e is accepted and included in all recent thermodynamic Table I.…”
Section: B Constitution and Invariant Reactions In The Fe-n-c Systemmentioning
confidence: 99%